Clinical epidemiological study of employees exposed to surfactant blend containing perfluorononanoic acid. Issue 9 (4th April 2007) - Mundt, Diane J; Mundt, Kenneth A; Luippold, Rose S; Schmidt, Michael D; Farr, Craig H
Abstract : Introduction: An epidemiological study was conducted of a perfluorononanoic acid (PFNA) surfactant blend, to investigate whether clinical differences were apparent between employees who were potentially exposed to the surfactant and those who were not exposed. The surfactant blend, which is related to other previously studied perfluorinated materials, is used in the production of some high-performance polymers. Methods: All 630 individuals employed at a polymer production facility using PFNA (CAS No 72968-38-8) at any time between 1 January 1989 and 1 July 2003 were included in the cohort. Plausibly related laboratory test results were abstracted from annual medical examination records, including liver enzyme function and blood lipids. Detailed work histories, available for all employees, provided the basis for determining exposure category. Thirty two clinical parameters were evaluated by exposure level at five points in time, determined to reflect changes in possible exposure intensity, as well as greatest number of records available. Annual cross-sectional analyses and longitudinal analyses that accounted for multiple measurements per person were conducted separately for men and women, by exposure groups. Results: Differences by exposure group for all laboratory measures, adjusted for age and body mass index, were small and not clinically significant. Although some statistically significant pair-wise differences were observed, these observations were not consistent between men and women, or over the five analysis windows. For the seven outcome variables (liver enzymes and blood lipids) examined in separate longitudinal models, no significant increase or decrease was observed by unit increase in cumulative exposure intensity score. Conclusion: This is the first epidemiological study investigating the possible health effects in humans associated with exposure to PFNA blend. Based on laboratory measures assessed over more than a decade, no adverse clinical effects were detected from occupational exposure to PFNA blend.